United States tea: A synopsis of ongoing tea research and solutions to United States tea production issues - D’Auria, John C.; Cohen, Stephen P.; Leung, Jason; Glockzin, Kayla; Glockzin, Kyle Mark; Gervay-Hague, Jacquelyn; Zhang, Dapeng; Meinhardt, Lyndel W. (Frontiers in Plant Science, 2022)
Tea is a steeped beverage made from the leaves of Camellia sinensis. Globally, this healthy, caffeine-containing drink is one of the most widely consumed beverages. At least 50 countries produce tea and most of the production information and tea research is derived from international sources. Here, we discuss information related to tea production, genetics, and chemistry as well as production issues that affect or are likely to affect emerging tea production in the USA. With this review, we relay current knowledge on tea production, threats to tea production, and solutions to production problems to inform this emerging market in the USA.